APLIKASI MOBILE INSTANT MESSAGING BERBASIS JAVA - Humdiana Roelly S.Kom., MM., M.Kom (Jurnal Informatika dan Bisnis, 2014)
Technology development in mobile phone stimulates the demand of application support that enables the device to maximize its potential to become smarter and make life easier. Mobile instant messaging as an instant messaging application via internet mobile is expected to provide user with unlimited mobility without losing access to information and communication. Instant messaging adalah teknologi yang memungkinkan komunikasi berbasis teks secara real-time antara dua orang atau lebih melalui jaringan internet atau jaringan lainnya (intranet). Mobile instant messaging adalah kemampuan instant messaging yang diimplementasikan pada perangkat mobile. Instant messaging is a technology that allows real-time text-based communication between two or more people over internet or other network (intranet). Mobile instant messaging is instant messaging ability implemented in mobile device. The mobile instant messaging application in this research is developed in Java environment (specifically Java ME), for the reason of its ability to run in any operating system and its open source authorization that allow supportive development and easy distribution. This research is initiated with literature study. User’s requirement is elicited with interview and exploration of similar application to gather system requirements for development. The system development is performed by using the method of object oriented analysis and design to build mobile instant messaging application in Java. The result of this developmental research is a Java based mobile instant messaging application with instant messaging and conference instant messaging features, which are competitively comparable to popular application, such as YMTiny, Yamee, eBuddy, Nimbuzz, and shMessenger. Moreover, this application is using local server to register user account, which allow faster connection speed for data transaction. This application is also enhanced with security encryption for packet data to ensure secure data transaction. The summary of this research is, Java based mobile instant messaging application offers local solution as an alternative to answer necessity for instant information and communication at affordable cost.